Association of Breakfast Skipping With Visceral Fat and Insulin Indices in Overweight Latino Youth - Alexander, Katharine E. (2009)
Few studies have investigated the relationship between breakfast consumption and specific adiposity or insulin dynamics measures in children. The goal of this study is to determine whether breakfast consumption is associated with adiposity, specifically intra-abdominal adipose tissue (IAAT), and insulin dynamics in overweight Latino youth. Participants were a cross-sectional sample of 93 overweight (≥85th percentile BMI) Latino youth (10–17 years) with a positive family history of type 2 diabetes. Dietary intake was assessed by two 24-h recalls, IAAT, and subcutaneous abdominal adipose tissue (SAAT) by magnetic resonance imaging, body composition by dual-energy X-ray absorptiometry, and insulin dynamics by a frequently sampled intravenous glucose tolerance test and minimal modeling. Participants were divided into three breakfast consumption categories: those who reported not eating breakfast on either day (breakfast skippers; n = 20), those who reported eating breakfast on one of two days (occasional breakfast eaters; n = 39) and those who ate breakfast on both days (breakfast eaters; n = 34). Using analyses of covariance, breakfast omission was associated with increased IAAT (P = 0.003) independent of age, Tanner, sex, total body fat, total body lean tissue mass, and daily energy intake. There were no significant differences in any other adiposity measure or in insulin dynamics between breakfast categories. Eating breakfast is associated with lower visceral adiposity in overweight Latino youth. Interventions focused on increasing breakfast consumption are warranted.